2021
DOI: 10.1055/s-0041-1740352
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Anti-NMDA Receptor Encephalitis in Ovarian Teratomas

Abstract: Background The rate of anti-N-methyl-D-aspartate receptor encephalitis (NMDARE) in ovarian teratomas is unknown. We aim to identify the prevalence of NMDARE as well as volumetric and histopathologic characteristics of ovarian teratomas in patients with versus without. Methods We performed a retrospective cohort study to identify patients with confirmed ovarian teratomas and the characteristics of teratomas in NMDARE compared with non-NMDARE patients. Patients aged between 0 and 21 years with confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Still, a few reports aimed at identifying the prevalence of anti-NMDAR encephalitis indicated that the rate of NMDAR encephalitis in ovarian teratomas is low, and NMDAR encephalitis patients have smaller teratomas than non-NMDAR encephalitis patients. They have concluded that further studies are needed to understand the timing of anti-NMDA receptor antibodies in teratomas and the development of NMDAR encephalitis [ 3 ]. The sensitivity of anti-NMDA receptor antibody testing is higher in CSF than in serum.…”
Section: Discussionmentioning
confidence: 99%
“…Still, a few reports aimed at identifying the prevalence of anti-NMDAR encephalitis indicated that the rate of NMDAR encephalitis in ovarian teratomas is low, and NMDAR encephalitis patients have smaller teratomas than non-NMDAR encephalitis patients. They have concluded that further studies are needed to understand the timing of anti-NMDA receptor antibodies in teratomas and the development of NMDAR encephalitis [ 3 ]. The sensitivity of anti-NMDA receptor antibody testing is higher in CSF than in serum.…”
Section: Discussionmentioning
confidence: 99%
“…According to the recent “Updated Diagnostic Criteria for Paraneoplastic Neurologic Syndromes”, NMDARe are considered neurologic syndromes at “intermediate risk”, associated with cancer in 30–70% of cases (mostly ovarian or extraovarian teratomas, such as mediastinal localizations), especially in females between 12 and 45 years of age (50% of all patients) [ 10 , 18 ]. On the other hand, women with ovarian teratomas generally have a low prevalence of anti-NMDAR antibodies, and those who develop autoimmune encephalitis seem to have smaller teratomas than those without NMDARe [ 10 ]. Meanwhile, paraneoplastic NMDARe are extremely rare in males and children under the age of 12 (less than 10%) [ 7 , 8 ].…”
Section: Definition Etiology and Pathophysiologymentioning
confidence: 99%
“…If the disease does not improve in 1–3 months after the beginning of first-line and second-line therapy, the use of cyclophosphamide can be considered at a dosage of 500–1000 mg/m 2 (maximum 1500 mg) in monthly pulses for up to 6 months. However, a primary tumour resection is the most important therapeutic step in paraneoplastic NMDARe [ 10 , 53 , 54 ]. Children with no teratoma-associated encephalitis have a less favorable response to therapy.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…3-5 Although rare, NMDA receptor encephalitis is more common than infectious encephalitis, including herpes simplex virus (HSV) and West Nile Virus encephalitis, in people <25 years old. 6 NMDA receptor encephalitis can develop as a paraneoplastic response to tumors, such as ovarian teratomas, 1,7 or after HSV encephalitis. 8 The presence of ovarian teratomas is more common in adolescents or adults compared to children.…”
mentioning
confidence: 99%